“Are you being serious, Frankenstein?” Transtextuality and Postmodern Tenets in Peter Ackroyd’s "The Casebook of Victor Frankenstein" - Miquel-Baldellou, Marta (Complutense Journal of English Studies, 2017)
This article is grounded on the premise that the story behind Mary Shelley’s novel Frankenstein; or the Modern Prometheus (1818) has acquired the status of a myth, which has been subjected to all sorts of adaptations that have ensured its current popularity. Looking into Frankenstein as a romantic text with certain traits that forestall postmodern theories, this study approaches Peter Ackroyd’s novel The Casebook of Victor Frankenstein (2008) as a postmodern adaptation of Mary Shelley’s classic through Gérard Genette’s inclusive critical term of transtextuality. With the aim to identify Ackroyd’s contribution to the myth of Frankenstein, this article analyses instances of intertextuality, insofar as Ackroyd’s text reproduces quotations from some of Mary Shelley’s autobiographical writings as well as from her seminal novel Frankenstein. Through displays of hypertextuality, Ackroyd’s postmodern novel also transforms Shelley’s original story resorting to metafiction, introducing changes in the structure and the focalisation of the narrative, and making use of parodic elements. Finally, Ackroyd’s postmodern novel also presents examples of metatextuality, inasmuch as it incorporates twists in the plot as a result of applying different critical readings of Mary Shelley’s seminal text.